2003
DOI: 10.1016/s0002-9270(03)00277-6
|View full text |Cite
|
Sign up to set email alerts
|

Portal pressure response to losartan compared with propranolol in patients with cirrhosis

Abstract: Losartan is as effective as propranolol in reducing portal pressure in cirrhotic patients who are not receiving diuretics. Losartan is also superior to propranolol for achieving target level hepatic venous gradient for prevention of variceal bleeding in nonascitic and alcohol-abusing cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Some studies showed benefit effect 14 , 15 but other papers showed that ARB was not appropriate to clinical use because of hazard effects such as hypotension and renal impairment with 26 or without portal pressure reduction. 14 , 15 , 26 , 27 As mentioned above, in the all previous study ARB was applied alone, and the effective dose was too high and resulted many complications such as renal impairment. Therefore in the present study we tried to compare ARB and NSBB combination therapy with NSBB monotherapy for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed benefit effect 14 , 15 but other papers showed that ARB was not appropriate to clinical use because of hazard effects such as hypotension and renal impairment with 26 or without portal pressure reduction. 14 , 15 , 26 , 27 As mentioned above, in the all previous study ARB was applied alone, and the effective dose was too high and resulted many complications such as renal impairment. Therefore in the present study we tried to compare ARB and NSBB combination therapy with NSBB monotherapy for the first time.…”
Section: Discussionmentioning
confidence: 99%
“… 13 However, AT1-R blockers alone did not show better effect than NSBB through many previous studies. 11 , 14 , 15 , 16 Therefore, this study aimed to identify the combination effect of ARB and NSBB comparing with NSBB monotherapy in reducing of PH.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging results were also obtained with the AA spironolactone [ 83 , 84 ] and with ARB/ ACEi therapy, in which significant reductions in HVPG compared with a placebo were reported [ 75 , 76 , 79 , 85 ]. Although greater reductions in HVPG were achieved with NSBBs than with ARBs/ACEis, the difference according to the pooled individual patient data was not significant [ 77 , 80 ]. The HVPG of Child-Pugh class A patients treated with ARBs/ACEis or NSBBs decreased by 17% and 21%, respectively, whereas there was no significant change in the HVPG of Child-Pugh class B/C patients treated with ARBs/ACEis (3%) [ 61 ].…”
Section: Ras Antagonists For the Treatment Of Hepatic Fibrosis And Pomentioning
confidence: 99%
“…Accordingly, progression of liver fibrosis in hepatitis C virus positive patients is significantly decreased after treatment with angiotensin-converting enzyme inhibitors [ 137 ]. AT II is crucially involved in the manifestations of renal fibrosis by induction of pro-fibrotic effector molecules and EMT resulting in enhanced ECM production [ 138 ], and inhibition of AT II using angiotensin-converting enzyme (ACE) inhibitors or blocking agents towards the AT I receptor has emerged as a therapeutic approach to slow down renal disease progression [ 139 ] and revealed anti-fibrotic actions in the lung, heart and liver [ 140 - 143 ]. Interestingly, all components of the RAS have been detected in the human colonic mucosa [ 144 ] and AT II is increased in the mucosa of CD patients [ 145 ].…”
Section: Reviewmentioning
confidence: 99%